High efficiency UMG silicon solar cells: impact of compensation on cell parameters. (6th December 2015) - Rougieux, Fiacre; Samundsett, Christian; Fong, Kean Chern; Fell, Andreas; Zheng, Peiting; Macdonald, Daniel; Degoulange, Julien; Einhaus, Roland; Forster, Maxime
Abstract: High efficiency solar cells have been fabricated with wafers from an n‐type Czochralski grown (Cz) ingot using 100% Upgraded Metallurgical‐Grade (UMG) silicon feedstock. The UMG cells fabricated with a passivated emitter and rear totally diffused (PERT) structure have an independently confirmed cell efficiency of 19.8%. This is the highest efficiency reported for a cell based on 100% UMG silicon at the time of publication. The current and power losses are analysed as a function of measured material parameters, including carrier mobility, lifetime and the presence of the boron–oxygen defect. Dopant compensation is shown to reduce both the minority carrier lifetime and mobility, which significantly affects both the current and voltage of the device. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : High efficiency solar cells have been fabricated with wafers from an n‐type Czochralski grown (Cz) ingot using 100% upgraded metallurgical‐grade (UMG) silicon feedstock. The UMG cells fabricated with a passivated emitter and rear totally diffused structure have an independently confirmed cell efficiency of 19.8%. This is the highest efficiency reported for a cell based on 100% UMG silicon at the time of publication.